ANALISIS PENGENDALIAN PERSEDIAAN PAKAN UDANG DENGAN METODE MIN-MAX STOCK PADA CV. IKHSAN JAYA - Ahmad Condro Widiyanto (LPPM Universitas Pekalongan, 2021)
CV. Ikhsanjaya is one of the companies focusing on shrimp farming, in which one of the types of shrimp feed used is SI-04. The problem faced by CV. Ikhsanjaya is the lack of shrimp feed stock in 2018 and 2019. The aim of this research is to find out the stock management of shrimp feed in CV. Ikhsanjaya that has been optimum to avoid surplus and lack of shrimp feed stock. Additionally, this research aims to find out the amount of shrimp feed stock, based on Min-Max Stock method, in CV. Ikhsanjaya to avoid surplus and lack of shrimp feed stock. Data is analyzed using min-max stock model. This method determines the minimal and maximum amount of shrimp feed stock, quantity of order, and so on. Based on the results of data analyzed, the calculation of the minimum and maximum amount of stock in 2018 show that the minimum amount of the final stock is 144.79 kilograms and the maximum amount of the final stock is 2,265.97 kilograms. Meanwhile, in 2019, the minimum amount of the final stock is 134.17 kilograms and the maximum amount of the final stock is 2229.97 kilograms.